Isolation and characterization of a myotoxin from Bothrops brazili Hoge, 1953 Hoge, 1953 snake venom (Ophidia: Viperidae). - Pantigoso, Carmen (2001)
A myotoxin from the venom of the snake Bothrops brazili has been purified by ion-exchange chromatography on CM-Sephadex C-50 with 0,05 M ammonium acetate buffer pH 7. The homogeneity was evaluated by PAGE with and without SDS, immunodiffusion and immunoelectrophoresis. The myotoxin is a basic protein with 15,6% of Lys+Arg; it is not a glicoprotein, has not enzymatic activity, and corresponds to 25% of the whole venom protein. The molecular weight of the myotoxin was determined by PAGE-SDS and gel filtration chromatography. The myotoxin has 30 KDa of molecular weight and two polypeptide chains of 15 KDa each. Myotoxin produces a severe necrosis on the gastrocnemius muscle of white mice. The myotoxin does not have hemolytic nor anticoagulant activity. However, produces edema with a DEM of 32,6 mg of protein.